The Effectiveness of Online Shopping Application as A New Market: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to determine the effectiveness of online shopping as a new market. Purposive sampling was enrolled in Grade 12 ABM Students in Bestlink College of the Philippines—the quantitative research design through questionnaires. The researchers used a quantitative approach, survey questionnaire, and purposive sampling for this study to gather information from the Grade 12 ABM students respondents. The respondents of the study were 50 selected in every section. The selected respondents are five students in ABM 1201-1210 sections. Time, product quality, payment method, discounts/promotions, website design/feature and convenience were figured out.  Furthermore, results showed that time, product quality, discounts/promotions, and convenience are the effective advantages of social media to businesses. With the help of proposed intervention or remediation to advantages, it lessens the e-commerce challenges. Based on the study results, the impact of online shopping is 1. Time- it helps to access a much larger range of products online, and search buttons make it easier to find the products you want in a minimal amount of time. 2. Product Quality- it helps to maintain customer satisfaction and loyalty and reduces the risk and cost of replacing faulty goods. 3. Payment Method- it helps customers pay quickly and save time and effort. 4. Discount and Promotion- discounts only refer to the price and actual sale of a product; promotions include a wide range of marketing and sales tactics that can begin before someone considers becoming a customer. 5. Website design/ Features- it helps to attract customer to purchase the product and gain more customers. 6. Convenience- it helps the customers decide what products to buy, what services to use, and what provides to engage.  The researchers recommend trying online shopping, and students should appreciate the effort of sellers and delivery riders to promote a fast and efficient marketplace. Customers should be careful when clicking and availing of the product. Seller researchers should consider the consumer expectations regarding the product's quality and quantity and fast product delivery. Future researchers should recommend online shopping to help other online sellers gain customers.